A UX community of practice: design goals, practice motivations and values - Hussein, Idyawati; Hussain, Azham; Mkpojiogu, Emmanuel O.C.; Mahmud, Murni (NADIA, 2019)
This research report provides an intuitive insight into the design goals, practice values and the motivations why practitioners involved in a community of practice are motivated to practice user experience design in industry. A survey approach with instrument having closed ended questions was utilized. The results indicated that the practitioners’ design goals followed a hierarchy, in the order: usability, functionality, security, pleasure and customizability. The strongest motivation driving respondents who attended the user experience (UX) gathering was performance oriented, hingedon classic competitiveness. In addition, the highest values among the respondents (UX designers) were to make users happy, followed by a focus on clients’happiness